Impact of a competition with two consecutive matches in a day on physical performance in young tennis players - Gallo-Salazar, C.; Del Coso, J.; Barbado, D.; Lopez-Valenciano, A.; Santos-Rosa, F. J.; Sanz-Rivas, D.; Moya, M.; Fernandez-Fernandez, J. (Applied Physiology, Nutrition, and Metabolism, 2017)
The purpose of this study was to analyze the effects of playing 2 tennis matches on the same day on physical performance in young tennis players. Twelve well-trained young tennis players took part in a simulated tennis competition consisting of 2 tennis matches on the same day (morning and afternoon sessions). Before and the day after the competition, physical performance was measured using a battery of countermovement jumps; a 10 m sprint; the 5-0-5 agility test; hip, grip and shoulder maximal isometric strength; shoulder range of motion; and a serve velocity test. Postcompetition results showed reduced performance in 10 m (-3.3%, effect size (ES) = small), dominant and nondominant 5-0-5 agility test (-4.6%, ES = moderate; -4.2%, ES = moderate, respectively), bilateral (-5.2%, ES = small), and unilateral countermovement jumps (dominant leg: -7.2%, ES = small; non-dominant leg: -9.1%, ES = small). Both dominant and nondominant shoulder external rotation range of motion increased (12.2%, ES = moderate; 5.6%, ES = small), whereas internal rotation decreased (-4.2%, ES = small; -3.3%, ES = small) in the postcompetition tests, together with the dominant shoulder external rotation (-10.7%, ES = moderate) and internal rotation (-9.3%, ES = small) strength. Physical impairments occurred in neuromuscular performance variables involving lower (e.g., jumping, sprinting, and change of direction) and upper (e.g., isometric strength and range of motion) limbs the day after playing a competition with 2 consecutive matches on the same day. These alterations in neuromuscular and sport-specific performance need to be taken into consideration when planning tournament schedules for young tennis players, as well as preparing match and recovery strategies.